KONTRIBUSI SELF-EFFICACY TERHADAP PRESTASI AKADEMIK MAHASISWA PKK UST - Anggri Sekar Sari (Jurnal Taman Vokasi, 2017)
This study aims to determine the effect of self-efficacy on improving student academic achievement. The research method used ex-post facto which was analyzed by linear regression analysis. The subjects of the study were students of PKK force of 2016/2017 with a population of 112 students and the calculation result of the sample was 98 students. Data collection techniques used are questionnaires and documentation. The instrument used is a questionnaire and Student Achievement Index. Test Validity 35 statement concerning instrument, whereas all instruments stated reliable with high reliability where 0,807> 0,7. The result of counting of normality test mentioned that count value> 0,05 which mean normal distribution data, whereas linearity test results where 0,025> 0,05 meaning linear data. Hypothesis testing includes simple linear regression analysis showing that F arithmetic (16,507)> F table (3,94) where probability value p (0,000) <0,05 meaning hypothesis accepted. The results of the study showed that self-efficacy had a positive effect on the improvement of student academic achievement.